3(x-4)(x-4)=27

Simple and best practice solution for 3(x-4)(x-4)=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-4)(x-4)=27 equation:



3(x-4)(x-4)=27
We move all terms to the left:
3(x-4)(x-4)-(27)=0
We multiply parentheses ..
3(+x^2-4x-4x+16)-27=0
We multiply parentheses
3x^2-12x-12x+48-27=0
We add all the numbers together, and all the variables
3x^2-24x+21=0
a = 3; b = -24; c = +21;
Δ = b2-4ac
Δ = -242-4·3·21
Δ = 324
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{324}=18$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-24)-18}{2*3}=\frac{6}{6} =1 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-24)+18}{2*3}=\frac{42}{6} =7 $

See similar equations:

| 100=22s+56 | | (6+x)^2=108 | | 4v=8=26-2v | | n/10+5=45 | | 5-(9/t)=-4/t^2 | | x=224/(1+9/100) | | 6d*2=5.2 | | -21w-10=24w+3 | | 13=x/3+2 | | x(x+2)=x2+2 | | (x+4)^2-5=0 | | X/10-7=9x= | | 2-7n=16 | | (6x-8)=(5x+14) | | 1/6x-(1/7x)+1/42x=6 | | -(v-4)=-6v+16 | | 79.8=7(m+3.8 | | 2n-7n=16 | | -2x+4=-2x+6 | | 3x+38+5x-32=180 | | 7x-(6)=36 | | -10(-2)+y=4 | | 1=-3w+64 | | -106+3x=38+9x | | 285=19n | | 48n+28=0 | | -6x+7x-8x=0 | | (3x-5)+(2x-25)=180 | | .15+.05x=1.05 | | 0.4h-3=-1 | | (w)/(5)-((w+3))/(w)=-(3)/(w) | | |y|+10=14 |

Equations solver categories